PERAN GENDER PADA SIKLUS MANAJEMEN BENCANA DI SEKTOR SOSIAL EKONOMI RUMAH TANGGA TANI (BENCANA ALAM GEMPABUMI DAN LETUSAN GUNUNGAPI) - Dina Ruslanjari; Dian Indira Wahyunita; Resi Sadewa Permana (Jurnal Kawistara, 2017)
The earthquake disaster in 2006 and the eruption of Merapi Volcano in 2010 have a different impact on the community activities in the province of Yogyakarta. The aims of this research are: (1) to analyze the role of gender based on differences in the characteristics of the Merapi eruption in Sleman and Bantul earthquakes; (2) to find the socio-economic variables which influence toward the role of gender in the characteristics of the Merapi eruption in Sleman and Bantul earthquakes. This research is using quantitative and qualitative methods. The research population is farming communities who live in the Padasan Sub-village of Sleman District and Serut Sub-village of Bantul District. Sampling technique is purposive. Data collection techniques are survey method, in-depth interview, and review of literature. Descriptive analysis was used to analyze the percentage of gender roles. Regression analysis was used to determine the variables that affect the gender role in social and economic. The results of the descriptive analysis show that there are similarities and differences in roles between men and women in the Serut Sub-village of Bantul District and Padasan Sub-village of Sleman District despite have a different disaster. Women in the daily cycle spent more time at home during days and nights to do housework. The results of regression analysis show that there is no influence of age, education, and income to the women role in the earthquake disaster in Serut Sub-village of Bantul District and volcano eruption in Padasan Sub-village of Sleman District.